Fundamentals of entrepreneurship (ENT300) Ezzymart / Muhammad Adli Mohamad... [et.al] - Mohamad, Muhammad Adli; Jamar, Mohd Syarif Akmal; Justin, Jerence; Abdul Rahman, Amir Shukri (2012)
Our company name is Ezzymart. The business is in partnership form consist of four partners. Each partner contributes certain amount of capital as agreed in our agreement. Our main business activity is online groceries. Our business will operate at Kuching, Sarawak. It will commence beginning 3rd JANUARY 2013. All partner are entitled to participate in the business management. After a detail discussion, we have agreed that Amir Shukri bin Abdul Rahman as our General Manager and Administration Manager, Muhammad Adli bin Mohamad as Marketing Manager, Jerence bin Justin as Operating Manager and Mhd Syarif Akmal Bin Jamar as Financial Manager.